2002
DOI: 10.3354/dao052029
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic analysis of viral haemorrhagic septicaemia virus (VHSV) isolates from France (1971-1999)

Abstract: The nucleotide sequences of a specific region of the glycoprotein gene were compared among 63 strains of viral haemorrhagic septicaemia virus (VHSV) isolated from fish in France between 1971 and 1999. The analysis was performed on a region corresponding to amino acids 238 to 331 of the glycoprotein gene, also designated the V2 region and previously shown to accumulate most of the mutations. The sequences of many VHSV isolates were found to be identical or very conserved. An isolate, designated L59X, obtained f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 15 publications
4
21
0
1
Order By: Relevance
“…To date, Genotype 3 included marine isolates from the North Sea/coastal waters of the British Isles together with 2 isolates recovered from outbreaks of VHS in Irish and Scottish turbot farms , Einer-Jensen et al 2004 as well as 1 isolate originating from eel caught in northern France (Thiéry et al 2002, Einer-Jensen et al 2004. Results obtained in the present study based on sequencing of a 335 nt region of the N gene indicated that the Flemish Cap isolates must also be grouped in Genotype 3, extending the geographic area in which this genotype is found to the eastern rim of the North Atlantic Ocean.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, Genotype 3 included marine isolates from the North Sea/coastal waters of the British Isles together with 2 isolates recovered from outbreaks of VHS in Irish and Scottish turbot farms , Einer-Jensen et al 2004 as well as 1 isolate originating from eel caught in northern France (Thiéry et al 2002, Einer-Jensen et al 2004. Results obtained in the present study based on sequencing of a 335 nt region of the N gene indicated that the Flemish Cap isolates must also be grouped in Genotype 3, extending the geographic area in which this genotype is found to the eastern rim of the North Atlantic Ocean.…”
Section: Discussionmentioning
confidence: 99%
“…It has a genome consisting of approximately 11 200 nucleotides and containing 6 genes (3' N-P-M-G-NV-L 5'). Initial nucleotide sequence analyses based on different regions of the glycoprotein (G) gene demonstrated the existence of 3 geographically distinct genotypes (Benmansour et al 1997, Stone et al 1997, Thiéry et al 2002. Sequence analysis of the nucleoprotein (N) gene has supported the existence of these 3 established genetic groups and, in addition, identified a new genotype (Snow et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Resale or republication not permitted without written consent of the publisher (Genotype Ia) along with a group of naturally occurring isolates originating from wild marine fish species residing predominantly within the Baltic Sea (Genotype Ib) (Benmansour et al 1997, Nishizawa et al 2002, Thiery et al 2002, Einer-Jensen et al 2004. Evidence suggests that an ancestor of marine Genotype Ib was the original source of introduction of VHSV into the rainbow trout industry (for review see Snow et al 2004).…”
Section: Abstract: Scophthalmus Maximus · Viral Haemorrhagic Septicamentioning
confidence: 99%
“…These genotypes reflect a largely geographic rather than a species-specific distribution. Genotype I includes a wide range of viruses originating from freshwater rainbow trout farms in continental Europe (Thiéry et al 2002, Einer-Jensen et al 2004) and a large number of isolates originating from marine species in the Baltic Sea, Skagerrak, Kattegat, and English Channel (Dixon et al 1997, Einer-Jensen et al 2004, Snow et al 2004. Genotype II includes a limited number of VHSV isolates recovered from the Baltic Sea (Snow et al 2004).…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%